Working Environment Selection After Pandemic Using Picture Fuzzy Sets - Bal, Mustafa; Uçal Sarı, İrem (Springer International Publishing, 2022)
After 2020, the behaviors of many industries about the working environment have changed rapidly, and remote working has become chosen significantly by many companies. The reason behind this behavior change is pandemic conditions. In current days, the most frequently asked question from a managerial perspective is whether to return to traditional working conditions or not. Even though a traditional working environment is still preferable for manufacturing industries, the service industry prefers remote-working such as banking, finance, software, and technology companies. In this paper, this question is considered and it is tried to answer for mentioned industries. Working environment change decision is not easy to answer when some criteria such as rent of office, efficiency, and usage of resources are considered; therefore, from a managerial perspective, decision making for working environment change is highly important. When the uncertainty of our world's pandemic condition is taken into account, making a decision gets more difficult. Analytical Hierarchy Process (AHP) with picture fuzzy sets is used to evaluate criteria to make the best decision under uncertainty. Software and technology companies are considered in the study to make evaluations by picture fuzzy AHP process. Based on the results of the analysis, performance-related factors and cost are determined as the most important criteria in the working environment selection.